Penerapan Nilai IMTAQ Siswa Melalui Pembiasaan Penguatan Pendidikan Karakter (PPK) di SMPN 21 Malang - Qurroti A`yun; Zahra `Arih Wicahya; Kurnia, Laila Tasa (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
In the process of habituation in character building, Religious Education becomes a very important thing to become a personality who has a tolerant attitude and becomes an effective medium to live a real life. The existence of this character formation effort is in line with one of the habituation programs that have been carried out at SMPN 21 Malang which provides a space to form IMTAQ-valued personalities in their students. The method used is descriptive qualitative with the type of case study because it aims to describe the state of the field that has been observed in depth and present it analytically in the form of interpretation of existing problems based on data sources. The data collection technique used is the triangulation technique (using 3 techniques at once: namely observation, interviews through online media, and observation) and is also supported by fidelity recordings. As for the results of the data obtained, there is a habituation program in the formation of IMTAQ valuable characters through an activity called